2009
DOI: 10.1293/tox.22.125
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tubular Cyst Formation in Newborn Rats Treated with p-Cumylphenol

Abstract: In this study, we investigated the sequential changes in the development of renal tubular cysts in newborn rats treated with p-cumylphenol (PCP). Fifteen animals per sex were treated orally with 300 mg/kg/day of PCP for up to 18 days from postnatal day (PND) 4 and were sacrificed on PNDs 8, 12, 19 and 22 and after a 7 day recovery period. On PNDs 8 and 12, slight dilatation of the collecting ducts was frequently observed in the medulla and slight papillary necrosis was also noted in some cases. These dilated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…3). Consistent with the high nuclear density, PCNA immunohistochemistry was strongly positive in the cystic epithelium as compared to the adjacent tubules 8 . However, no polypoid or papillary proliferation was noted, and the hyperplastic lining epithelium remained in a cuboidal to columnar form within a simple monolayer.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…3). Consistent with the high nuclear density, PCNA immunohistochemistry was strongly positive in the cystic epithelium as compared to the adjacent tubules 8 . However, no polypoid or papillary proliferation was noted, and the hyperplastic lining epithelium remained in a cuboidal to columnar form within a simple monolayer.…”
supporting
confidence: 71%
“…They are associated with a wide spectrum of chemical groups, including pcumylphenol (PCP), a chemical used as lubricants, surfactants, insecticides and phenolic resins 7 . A previous investigation focused on morphologically characterizing cystic kidneys induced in rat neonates when dosed with PCP for 18 days from postnatal day (PND) 4 revealed that treatment with PCP resulted in the sequential formation of cystic tubules in rat neonates 8 . A follow-up investigation was carried out to determine the critical dosing period for PCP to develop cystic kidneys in rat neonates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the 1/2Nx rats showed renal tubular dilatation 84 days later, but there was no evidence of progression of marked fibrosis or glomerular lesions. An increase in the number of PCNA-positive cells has been shown to correlate with renal tubular regeneration and cystic formation [38,39]. Therefore, the increased number of PCNA-positive epithelial cells in DEK-DM is considered to reflect the increased number of renal tubules and the progression of tubular dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was concord with Tootian et al [15,25] that demonstrated high percent of creatinine, blood urea nitrogen, alkaline phosphatase which consider waste products of protein metabolism that excreted by the kidney and give indicators of kidney destruction. In other study was Conducted on rat reveal that nitrophenol compound cause deformity in the shape of mitochondria with dense deposits in the basement membranes of the glomeruli was noted in electron microscope [15,27,28].…”
Section: Discussionmentioning
confidence: 99%